Evaluation of the Flexural Performance and CO2 Emissions of the Voided Slab - Seungho Cho; Seunguk Na (Advances in Materials Science and Engineering)
Reinforced concrete is regarded as one of the ideal structural materials which comprises concrete with high compressive strength and reinforcing bars with high tensile strength. However, concrete has been pointed out that it consumes a large volume of energy and emits a lot of carbon dioxide during its manufacturing. In order to lower such environmental burdens of concrete structures, a number of studies and approaches have been carried out. The voided slab is also suggested as a new method to reduce the environmental burden since voided section of the slab would use less concrete compared with the normal reinforced concrete slab. However, no studies have evaluated the CO2 emissions and environmental performance of voided slabs. The purpose of this study was to evaluate the structural performance of voided slabs and empirically corroborate their environmental influence. The flexural performance test was carried out based on the variables of the depth of slab, types of the void former materials, and the hollowness ratio. In addition, comparison of the emission of CO2 was also performed by considering the hollowness ratio and types of void former materials over the normal reinforced concrete slab. The structural performance of the voided slab was similar or slightly higher than the normal reinforced concrete slab. The yield strength of specimens was increased approximately 10∼30% over the anticipated yield strength. Based on this result, it is considered that the voided slab would be sufficient to structural performance and beneficial to plane planning in buildings. In general, it is considered that the voided slab would be beneficial to both structural and environmental aspects. However, the test results in this research showed that the voided slab would emit more carbon dioxide emissions compared to the normal reinforced concrete slab. The main source of more CO2 emissions in the voided slab was the anchoring materials. In this research, wires were used to fix the void former materials to the reinforcing bars. In order for the voided slab to become a more eco-friendly and sustainable material, new anchoring methods such as use of recycled materials, new void former materials without anchoring, or other eco-friendly materials should be applied to reduce the emission of CO2.